Analisis Persepsi Perawat Terhadap Prevalensi Perilaku Agresif Pasien di Rumah Sakit Jiwa X - Muchamad Hardoko (Jurnal Admmirasi, 2020)
The purpose of this study was to determine the nurses' perceptions at Grhasia Mental Hospital about aggressive behavior of patients at the Mental Hospital x. This research is a mixed method research, namely Sequential Explanatory. This mixed method research aims to obtain data and information to complement each other's description of the results of the study of the phenomenon under study and to strengthen research analysis. The conclusion that can be drawn from the results of this study is that the perception of nurses at the Ghrasia Mental Hospital is in the positive realm with a percentage of 63.7%. The prevalence of aggressive behavior of patients who endanger nurses is mostly in the category of ever, but with the level of behavior that can still be overcome. The tendency of aggressive behavior is in the form of physical threats with a percentage of 92.2%. There is a positive influence between perceptions on the patient's aggressive behavior that endangers the nurse. This positive value can be seen from the significance which indicates the number 0,000 and the Pearson Spearman rank value 0.922 **.